1980
DOI: 10.1017/s0003356100023941
|View full text |Cite
|
Sign up to set email alerts
|

Genetic size-scaling rules in animal growth

Abstract: Striking similarities are known to exist in the growth processes of different mammalian genotypes. Two genetic size-scaling rules formally summarize these well-established similarities. In consequence, experimental results in one breed or species can often provide an excellent quantitative guide to biological relationships in other species. Despite strong genetic similarity, much genetic diversity usually remains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
1
2

Year Published

1986
1986
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 6 publications
3
55
1
2
Order By: Relevance
“…Although all these models recognize the need for genetically driven trajectories (either explicitly or implicitly), they do not invoke (physiological state dependent) genetic expression, but instead use time as the driver to generate the homeorhetic trajectories. This may seem like a detail, but studies of growth have shown that relating trajectories to measures of physiological state, for example, degree of maturity, greatly extends the ability of models to accommodate genotype differences (Taylor, 1980;Emmans and Kyriazakis, 2001;Doeschl-Wilson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although all these models recognize the need for genetically driven trajectories (either explicitly or implicitly), they do not invoke (physiological state dependent) genetic expression, but instead use time as the driver to generate the homeorhetic trajectories. This may seem like a detail, but studies of growth have shown that relating trajectories to measures of physiological state, for example, degree of maturity, greatly extends the ability of models to accommodate genotype differences (Taylor, 1980;Emmans and Kyriazakis, 2001;Doeschl-Wilson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The notion of teleonomic trajectories is not new; it is implicit in the idea of potential curves of, for example, growth or lactation, as these imply a genetically driven performance goal. Models that seek to describe potential growth have a long history (see Taylor, 1980;Emmans, 1997), and lactation models explicitly aimed at describing potential have also been proposed (Friggens et al, 1999). Interestingly, the model of Friggens et al (1999) based on a heuristic view of milk production turns out to be the same as the model of Dijkstra et al (1997) derived from a mechanistic view.…”
Section: Introductionmentioning
confidence: 99%
“…Intake of different sheep breeds at a BW may vary with mature BW, called A. Taylor (1980) proposed 2 genetic size-scaling rules. The first was to treat all time variables, such as daily feed intake, as proportional to A 0.73 .…”
Section: Introductionmentioning
confidence: 99%
“…Because of the differeqt gmwth rates 40% and 500/0). For a detailed comparison between hybrid groups, the effect of genetic size scaling (Taylor, 1980) may be an interesting aspect for further study.…”
Section: Resultsmentioning
confidence: 99%